STUDI HUKUM ATAS PENYIMPANGAN WEWENANG KEPALA DESA DALAM PENGELOLAAN DANA DESA TERKINI - Hidayatullah, Sulthon; Wicaksono, Demas Brian; Soetijono, Irwan Kurniawan (TAHKIM, 2025)
As an archipelagic nation with a vast territory, Indonesia prioritizes decentralization as a key strategy, one of which is granting villages autonomy to regulate and manage their own finances. However, the practice of abuse of authority by village heads in managing village funds remains common, resulting in corruption and declining public trust in village government. This study aims to analyze the legal aspects and oversight system for abuse of authority by village heads based on the provisions of Law Number 3 of 2024, amending Law Number 6 of 2014 concerning Villages. The approach used in this study is a normative juridical approach, using statutory analysis and a conceptual approach. Data sources were obtained from legal literature and other related documents. The results indicate that although regulations prohibiting and sanctioning abuse of authority exist, oversight is still suboptimal. Village heads found to have violated the law can be subject to administrative or criminal sanctions depending on the severity of the offense. Ideally, village fund oversight should be carried out in an integrated manner through internal mechanisms by the Village Consultative Body, external oversight by state institutions such as the Supreme Audit Agency (BPK) and the Inspectorate, and through active community involvement. The conclusion of this study emphasizes the need to strengthen the oversight function, increase the capacity of village heads and their staff, and utilize information technology in budget reporting to achieve transparent, accountable, and public-interest village fund management. Keywords: village head authority, village funds, legal oversight, accountability